Understanding COVID-19 Vaccine Hesitancy among Tertiary Level Students in Malaysia Using the 5C Model - A Short Survey - Pratama Putri, Novia; Subramaniam, Geetha; Sivasamugham, Lalita Ambigai; Gopinathan, Sharmini; Raman, Murali; Hai, Sam Toong (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To explore the attitudes of the tertiary level students in Malaysia towards COVID-19 vaccines to analyze the leading cause of vaccine hesitancy among this group. Methodology: A cross-sectional study was conducted from January to February 2021 among undergraduates from 5 different private tertiary institutions across Malaysia. The data was obtained through an online survey using Google Forms and analyzed using Smart PLS 3 software. Results: The validity of the measurement model led to the structural model after bootstrapping. From the data analysis, it was confirmed that Collective Responsibility and Confidence had a significant positive relationship with vaccine hesitancy, while complacency, constraints and calculation did not seem to contribute to vaccine hesitancy Conclusion: Most respondents have good knowledge about the vaccines and generally have a positive attitude towards COVID-19. The respondents were hesitant to get the COVID-19 vaccines because they were concerned about the safety and efficacy of the COVID-19 vaccines as they are new and rapidly developed. KeyWords: COVID-19, vaccine hesitancy, tertiary level students, Malaysia